Pengaruh Penambahan Tepung Daun Kelor (Moringa oleifera) Terhadap Kandungan Vitamin C dan Organoleptic Pada Tempe - ALI SABARUDIN; Nurwati; Daryono; Melly Fera (Fakultas Pertanian, Universitas Warmadewa, 2023)
Tempeh is a processed vegetable product made from legumes. Tempeh has a softer texture than soybeans, because the tempeh mold digests the matrix between the cells of soybean seeds, so that the cells are separated from the surrounding materials. Efforts to improve the quality of tempeh by adding Moringa (Moringa Oliefera) leaf extract were carried out in this study. The purpose of this study was to determine the effect of the addition of Moringa leaf extract on tempeh and determine the vitamin C content and organoleptic on tempeh. This method that I used was an experimental method with a complete randomized design (CRD) with 6 treatments and each repeated four times. The treatments were the addition of moringa leaf extract at 0%, 1%, 2%, 3%, 4%, and 5%. The analysis was conducted on vitamin C content and organoleptic test. The results of this study showed that the addition of moringa leaf extract had a significant effect on the protein, fat, and carbohydrate content of tempeh. The addition of moringa leaf extract as much as 5% increased the protein content by 1.47% fat by 1.41% and carbohydrates by 0.70%, tempeh with the addition of moringa leaf extract 4% and had the best value in all aspects of the organoleptic test, namely aroma, taste, texture and color. The conclusion of this study is the addition of moringa leaf extract affects the vitamin C content and organoleptics in tempeh.